Craniofacial implants in a failed autologous reconstruction of microtia: a case report - Vladimir Frias (SpringerOpen, 2021)
Abstract Plastic surgical reconstruction is considered to be the gold standard for the repair of microtia as the results are permanent and constructed from the patient's own tissue; however, the multiple surgeries required and the difficulty in attaining adequate cosmetic results often result in patients choosing a prosthesis as a long-term rehabilitation. Advances in osseointegration in the craniofacial region have improved the outcomes with auricular prosthetics by providing a reliable method of attachment of the prosthesis and increasing patient acceptance. A case presentation illustrates the results of both treatment modalities and examines the outcomes on the same patient.